Morphological Plasticity of the Retina of Viperidae Snakes Is Associated With Ontogenetic Changes in Ecology and Behavior - Tashiro, Juliana H.; Ventura, Dora F.; Hauzman, Einat (Frontiers in Neuroanatomy, 2022)
Snakes of the Viperidae family have retinas adapted to low light conditions, with high packaging of rod-photoreceptors containing the rhodopsin photopigment (RH1), and three types of cone-photoreceptors, large single and double cones with long-wavelength sensitive opsins (LWS), and small single cones with short-wavelength sensitive opsins (SWS1). In this study, we compared the density and distribution of photoreceptors and ganglion cell layer (GCL) cells in whole-mounted retinas of two viperid snakes, the lancehead Bothrops jararaca and the rattlesnake Crotalus durissus, and we estimated the visual acuity based on anatomical data. The ground-dwelling C. durissus inhabits savannah-like habitats and actively searches for places to hide before using the sit-and-wait hunting strategy to ambush rodents. B. jararaca inhabits forested areas and has ontogenetic changes in ecology and behavior. Adults are terrestrial and use similar hunting strategies to those used by rattlesnakes to prey on rodents. Juveniles are semi-arboreal and use the sit-and-wait strategy and caudal luring to attract ectothermic prey. Our analyses showed that neuronal densities were similar for the two species, but their distributions were considerably different between and within species. In adults and juveniles of C. durissus, cones were distributed in poorly defined visual streaks and rods were concentrated in the dorsal retina, indicating higher sensitivity in the lower visual field. In adults of B. jararaca, both cones and rods were distributed in visual streaks, while in juveniles, rods were concentrated in the dorsal retina and cones in the ventral retina, enhancing sensitivity in the lower visual field and visual acuity in the upper field. The GCL cells had peak densities in the temporal retina of C. durissus and adults of B. jararaca, indicating higher acuity in the frontal field. In juveniles of B. jararaca, the peak density of GCL cells in the ventral retina indicates better acuity in the upper field. The estimated visual acuity varied from 2.3 to 2.9 cycles per degree. Our results revealed interspecific differences and ontogenetic plasticity of the retinal architecture associated with changes in the niche occupied by viperid snakes, and highlight the importance of the retinal topography for visual ecology and behavior of snakes.